Novel diagnostic processes and challenges in bronchoscopy - Zsolt Pápai-Székely; Gábor Grmela; Veronika Sárosi (Frontiers Media S.A., 2024)
Diagnostic bronchoscopy is a minimally invasive procedure that plays a crucial role in the diagnosis and management of various respiratory conditions. This paper explores the advancements in technology that have revolutionized the field and focuses on the new diagnostic procedures in bronchoscopy that have emerged in recent years. These innovative techniques have expanded the diagnostic capabilities of bronchoscopy, allowing for more accurate and comprehensive evaluation of respiratory conditions. This paper will also discuss the challenges in the diagnostic process with bronchoscope.